READING MISCUE ANALYSIS OF SECOND SEMESTER STUDENTS IN STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - HAPSARI, SHERLIE DWI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Reading is one of language skills that is important to be mastered. Reading can help the reader to get new information and knowledge through printed media. Reading miscue analysis is one of the main research instruments in reading. As readers, it is important to know their own strategy and skills when reading the text, and Retrospective Miscue Analysis (RMA) can help them to discover it. In RMA, the students are asked to read the text orally, retell the context and discuss together with the writer. The writer conducts a study on reading miscue analysis of three good readers of second semester students in Study Program of English of Universitas Brawijaya. There are two problems in this study: (1) What oral reading miscues do the good reader of second semester students in Study Program of English make? (2) Why do the good readers of second semester students in Study Program of English do the oral reading miscues?In this study, the writer analyses the types of miscue by using theory of Goodman and Burke (1973) and the three cueing systems by using Goodman’s theory (1969). This research used a qualitative method because this study focused on the depth of understanding and the writer records the process of collecting the data.The results of this research showed that even a good reader produced miscues and there were fifty nine (59) miscues, 20 omissions (34%), 17 mispronunciations (29%), 9 substitutions (15%), 8 self-corrections (14%), 3 insertions (5%) and 2 repetitions (3%). There was no reversal miscue produced by the students. The three of the students were good reader, because in retelling session they could predict the word that they did not know and could make a general conclusion in the text. Their skills were good, because they were fluent when reading the text and they were able to comprehend the text.This research hopefully can help the participants to know their own strength and weakness in reading and can be the additional source or teaching materials for the lecturers. The writer hopes it can give new contribution for the next researcher to conduct the same research in different object. Keywords: Reading, Miscue, Miscue Analysis, Retrospective Miscue Analysis, Good Reader